(untitled) (Alternate Horizons, 2022)
Human Rights Day has become an iconic date in South Africa’s history and is a reminder of our rights and the cost paid for these rights. Unfortunately, many South Africans, specifically women and the LGBTQ+ community continue to suffer human rights violations and South Africans need to reflect on their own role in influencing change in the right direction.